Eksperimen Gabungan Teknik Reduksi PAPR Dan Predistorsi Pada Sistem OFDM Menggunakan USRP - Gunawan, M Wisnu; Arifin, Arifin; Moegiharto, Yoedy; Budikarso, Anang; Briantoro, Hendy (Majalah Ilmiah Teknologi Elektro, 2024)
In this paper, the performances of the joint technique of PAPR Reduction with ICF method and predistortion with inverse Saleh model on OFDM system are evaluated. The system’s performances at the receiver are presented by constellation nodes of QAM symbols  From the experiment results can be shown that the predistorstion improves the system’s performance since the spreading of constellation nodes became smaller. While the performances of PAPR reduction technique are shown as the PAPR reduction values for clipping ratio (CR) values of 5, 4 and 3. The PAPR reduction values are 7,6 dB, 8,4 dB and 9,4 dB. And the predistortion technique can reduce the PSD gain of OFDM signal and linear high power amplifier of 30 dB.